Academic Procrastination as a Bridge Between Adaptive Perfectionism and Psychological Well-Being: Mindfulness As Moderating - Rohmawan Adi Pratama; Purwati Purwati; Muhammad Japar; Indah Novita Sari; Filda Khoirun Nikmah (Universitas Katolik Soegijapranata, 2025)
This study explores how adaptive perfectionism influences academic procrastination and psychological well-being, with mindfulness serving as a moderating factor. A total of 155 university students in Surakarta participated in this research, selected through random sampling. Using a quantitative approach, the study employed Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine both mediation and moderation effects. The findings reveal that adaptive perfectionism has a positive impact on psychological well-being while simultaneously reducing academic procrastination. However, academic procrastination negatively affects psychological well-being and partially mediates the relationship between adaptive perfectionism and well-being. Additionally, mindfulness plays a crucial moderating role, strengthening the ability of individuals with high mindfulness to manage perfectionist tendencies and reduce procrastination. These results underscore the importance of fostering mindfulness practices to minimize the adverse effects of academic procrastination and enhance students' overall well-being.